Answers

2016-02-20T15:15:43+05:30
So, here it is..
[(√5-2)/(√5+2)]-[(√5+2)/(√5-2)]
=[
(√5-2)/(√5+2)*(√5-2)/(√5-2)]-[(√5+2)/(√5-2)*(√5+2)/(√5+2)]
multiplied 
(√5+2) & (√5-2) both sides
=[
(√5-2)²/5-4]-[(√5+2)²/5-4]
=[5-4√5+4]-[5+4√5+4]
=5-4√5+4-5-4√5-4
=-8
√5

Hope it helped. ^_^
2 4 2
2016-02-21T08:05:22+05:30
We can do like this also,{(√5-2)/(√5+2)-{(√5+2)/(√5-2)}                                   sqaring on both sides to(√5+2)and (√5+2)                                                                                          {(√5-2)/(√5+2)}²-{(√5+2)²/(√5-2)                                                                       {(√5-2)/(5+4)}-{(5+4)/(√5-2)}                                      now squaring on both sides (√5-2) and (√5-2)                                                                                      {(√5-2)²/(9)}-{(9)/(√5-2)²}                                                                                 {(5-4)/(9)}-{(9)/(5-4)                                                                                           (1/9)-(9/1)=1/9-9/1=1-81/9=80/9=8.8888888888888888...................................    
1 4 1